2023
DOI: 10.1002/epi4.12727
|View full text |Cite
|
Sign up to set email alerts
|

The genetic link between systemic autoimmune disorders and temporal lobe epilepsy: A bioinformatics study

Abstract: Objective:We aimed to explore the underlying pathomechanisms of the comorbidity between three common systemic autoimmune disorders (SADs) [i.e., insulin-dependent diabetes mellitus (IDDM), systemic lupus erythematosus (SLE), and rheumatoid arthritis (RA)] and temporal lobe epilepsy (TLE), using bioinformatics tools. We hypothesized that there are shared genetic variations among these four conditions. Methods: Different databases (DisGeNET, Harmonizome, and Enrichr) were searched to find TLE-associated genes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Malekpour et al. ( 16 ) explored the relationship between frontal lobe epilepsy and three immune disorders, including RA, and showed that there were common genetic variants among the conditions. In addition, a meta-analysis emphasized that patients with RA have a higher risk of epilepsy than non-RA patients, and there was a negative correlation with age.…”
Section: Discussionmentioning
confidence: 99%
“…Malekpour et al. ( 16 ) explored the relationship between frontal lobe epilepsy and three immune disorders, including RA, and showed that there were common genetic variants among the conditions. In addition, a meta-analysis emphasized that patients with RA have a higher risk of epilepsy than non-RA patients, and there was a negative correlation with age.…”
Section: Discussionmentioning
confidence: 99%